Meningkatkan Kepenulisan Karya Ilmiah Bagi Guru PP. Mambaus Sholihin dan Civitas Kampus UNKAFA Suci Manyar Gresik - Faizin, Nur; Rizal Ramadhan, Mochammad; Basid, Abdul; Fauzan, Moh. (Jurusan Ilmu Pendidikan - Universitas Lampung, 2023)
Literacy and scientific writing skills are still limited among teachers and students at Ponpes Mambaush Sholihin. One of the causes is a lack of understanding of the rules of scientific writing. Difficulty in expressing thoughts in writing also poses a challenge. This article is the result of a service project aimed at enhancing literacy and scientific writing at Ponpes Mambaush Sholihin Gresik through the Participatory Action Research (PAR) approach. The findings of the project indicate that literacy and scientific writing skills are still limited among teachers and students. Lack of understanding of writing rules and difficulty in expressing thoughts are the main challenges. Through the PAR approach, the project provided training to teachers and students, involving stages of preparation, implementation, mentoring, and evaluation. The results showed an improvement in understanding the rules and techniques of scientific writing. The PAR approach serves as a solution to build awareness and enhance scientific writing skills at Ponpes Mambaush Sholihin Gresik. The project's findings also emphasize the importance of literacy and scientific writing in academic development and teaching, as well as expanding the benefits of research findings through publication